PTU-117 Sequential NUC therapy following pegylated interferon provides a greater decline in HBSAG and potentially offers a treatment advantage over current therapies. (22nd June 2015) - Gill, US; Hansi, NK; Payaniandy, L; Schulz, J; Payaniandy, D; Alazawi, W; Dearden, J; Kallis, YN; Kooner, P; Marley, R; Tong, W; Foster, GR; et al.
Abstract : Introduction: Tenofovir and Entecavir are potent nucleots (t)ide analogues (NUCs) and are the standard of care in the treatment of Chronic Hepatitis B (CHB). Despite this, they have limited ability to reduce HBsAg, thus indefinite or life-long therapy is mandated in the majority of patients. Pegylated-Interferon-Alpha (PegIFNa) is associated with better rates of HBsAg decline, but its effect is limited to a small proportion of patients. In isolation, these therapies are inadequate. By optimising the use of these therapies, delivered in combination or sequentially, better treatment outcomes may be achievable. We report on the treatment response in a cohort of patients treated with sequential NUC therapy. Method: 31 patients (male = 25); median age 32 (range 18–55), HBeAg positive (n = 20), were treated with PegIFNa; deemed non-responders and treated sequentially with a NUC analogue. Treatment response in this cohort was compared with 58 patients (male = 50); median age 45 (range 21–72), HBeAg positive (n = 25) who were treated with do-novo NUC therapy without previous PegIFNa exposure. Patients in both cohorts were virally suppressed at the time of analysis. Serum ALT, HBV DNA and HBsAg were quantified at baseline and longitudinally in the cohorts. Results: In the sequential NUC therapy group, baseline median ALT was 102 IU/L (range 24–420) and median HBV DNA 6.93 logIU/ml compared with 43 IU/L and 4.48 logIU/ml respectively for the de-novo NUC group. ALT normalisation and reduction in HBV DNA to undetectable levels was similar in both groups over follow-up (p = n.s). At the time of viral suppression (9–12 months in both cohorts) the decline in HBsAg in the de-novo NUC group overall was 0.02 logIU/ml compared to baseline (p = n.s). In patients receiving sequential NUC therapy there was a significant decline in HBsAg over follow-up compared to baseline (0.70 log IU/ml, p = 0.0001). Conclusion: Sequential NUC therapy following treatment failure with PegIFNa is associated with greater reductions in HBsAg than PegIFNa alone or NUC monotherapy. This suggests PegIFNa may prime the immune response, even in the context of treatment failure, leading to better outcomes with sequential NUC therapy. We have identified an immune phenotype associated with HBsAg decline in sequential NUC therapy. Further studies are required to confirm this finding and the applicability of an immune marker to predict treatment response in clinical practice. Disclosure of interest: None Declared.